Fractional Derivatives Applied to Epidemiology - Monteiro, N. Z.; Mazorche, S. R. (Trends in Computational and Applied Mathematics, 2021)
We seek investigate the use of fractional derivatives, both analytically and through simulations. We derivate some models and perform investigations about them, discussing difficulties and differences between classic and fractional models. Also, we analyzed the COVID-19 pandemic using a fractional epidemiological SIR model and performed a numerical analysis using finite differences and implementation in MATLAB.